Changes in the Subdoligranulum genus in patients with autoimmune disease: a systematic review and meta-analysis - Shen, Lu; Zhao, Ying; Liu, Shuting; Li, Shangfeng; Li, Qian; Tung, Tao-Hsin; Shen, Bo (Frontiers in Immunology, 2025)
BackgroundAutoimmune diseases have different pathogenic mechanisms but share underlying patterns of gut microbiome perturbation and intestinal barrier dysfunction. Recent evidence suggests that an arthritogenic strain of Subdoligranulum causes a local inflammatory response in the gut. Therefore, the aim of this review was to systematically summarize the relationships between Subdoligranulum and multiple autoimmune diseases.ObjectiveTo evaluate the changes of Subdoligranulum in different autoimmune diseases.MethodsFour databases, including PubMed, Cochrane, Web of Science, and Embase, were searched up to June 17, 2025, to identify studies that detected Subdoligranulum in autoimmune diseases. A meta-analysis was conducted to compare the differences in Subdoligranulum between healthy people and patients with autoimmune diseases, and the changes in these bacteria under different treatments were compared for similar diseases. The relationships between Subdoligranulum and inflammation-related biomarkers were also analyzed.Study selectionWe included articles that addressed both autoimmune diseases without intervention and the detection of Subdoligranulum in feces, and we presented a description of changes in bacteria in patients and healthy controls.Quality assessmentWe used the Newcastle–Ottawa Scale (NOS) to independently assess the methodological quality of the case–control studies. The Journal of Biomedical Informatics (JBI) critical appraisal checklists were utilized to assess the quality and risk of bias in cross-sectional studies.ResultsTwelve studies were included. These studies were conducted in four different countries and included a total of 1,792 participants (patients with autoimmune disease and healthy controls). Our meta-analysis results indicate that, compared with healthy controls, most patients with autoimmune diseases included in the study had lower levels of Subdoligranulum (p = 0.027). In addition, it was found that bacteria were associated with several inflammation-related biomarkers. For example, bacterial levels were positively correlated with C-reactive protein (CRP), lipopolysaccharide (LPS)-binding protein (LBP), and Treg cells. However, the levels were negatively correlated with IL-8. These relationships may underlie both the occurrence and development of autoimmune diseases.ConclusionThe abundance of Subdoligranulum in patients with organ-specific autoimmune diseases was decreased, whereas no consistent findings were observed for systemic autoimmune diseases.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024543767, identifier CRD42024543767.